Proteomic and Metabolite Profiling Reveals Profound Structural and Metabolic Reorganization of Adipocyte Mitochondria in Obesity. Issue 3 (7th February 2020) - Schöttl, Theresa; Pachl, Fiona; Giesbertz, Pieter; Daniel, Hannelore; Kuster, Bernhard; Fromme, Tobias; Klingenspor, Martin
Abstract : Objective: Previous studies have revealed decreased mitochondrial respiration in adipocytes of obese mice. This study aimed to identify the molecular underpinnings of altered mitochondrial metabolism in adipocytes. Methods: Untargeted proteomics of mitochondria isolated from adipocytes and metabolite profiling of adipose tissues were conducted in diet‐induced obese (DIO) and lean mice. Subcutaneous and intra‐abdominal adipose tissues were studied to depict depot‐specific alterations. Results: In subcutaneous adipocytes of DIO mice, changes in proteins related to mitochondrial structure and function were observed. Mitochondrial proteins of the inner and outer membrane were strongly reduced, whereas proteins of key matrix metabolic pathways were increased in the obese versus lean state, as further substantiated by metabolite profiling. A pronounced decrease in the oxidative phosphorylation (OXPHOS) enzymatic equipment and cristae density of the inner membrane was identified. In intra‐abdominal adipocytes, similar systematic downregulation of the OXPHOS machinery in obesity occurred, but there was no regulation of outer membrane or matrix proteins. Conclusions: Protein components of the OXPHOS machinery are systematically downregulated in adipose tissues of DIO mice compared with lean mice. Loss of the mitochondrial OXPHOS capacity in adipocytes may aggravate the development of metabolic disease.